2021
DOI: 10.3389/fsufs.2021.709267
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus spp. and Bacillus spp. as Growth Promoters in Cotton Plants Under Greenhouse Conditions

Abstract: This study aimed to verify the potential of three Aspergillus and Bacillus species as growth promoters in cotton plants under greenhouse conditions. The experiment was conducted with a completely randomized design with seven treatments (six microorganisms plus one control) and five replicates until the flowering stage at 70 days after emergence. The inoculation of cotton plants with Bacillus velezensis (Bv188) and Bacillus subtilis (Bs248 and Bs290) had a positive effect on total nitrogen extraction (899.31, 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Interestingly, the B. subtilis bacterium used in the present study has several plant growth-promoting characteristics, such as biological nitrogen fixation, phosphorus solubilization, and indole acetic acid production, as has been demonstrated in previous studies in soybean, corn and cotton crops (Lobo et al, 2019;dos Santos et al, 2021;Escobar Diaz et al, 2021a). Different plant organs have different ways of being colonized by microorganisms (Compant et al, 2021).…”
Section: Discussionmentioning
confidence: 57%
“…Interestingly, the B. subtilis bacterium used in the present study has several plant growth-promoting characteristics, such as biological nitrogen fixation, phosphorus solubilization, and indole acetic acid production, as has been demonstrated in previous studies in soybean, corn and cotton crops (Lobo et al, 2019;dos Santos et al, 2021;Escobar Diaz et al, 2021a). Different plant organs have different ways of being colonized by microorganisms (Compant et al, 2021).…”
Section: Discussionmentioning
confidence: 57%
“…In this regard, A. sydowii is a halophilic fungus commonly found in different marine ecosystems and is considered a model organism for studying molecular adaptations of filamentous fungi to hyperosmolarity [ 37 ]. Recent studies showed that A. sydowii enhances plant growth by stimulating phosphorus solubilization in maize [ 38 ] and promoting higher phosphorus absorption by cotton plants [ 39 ]. The marine A. versicolor is a siderophore producer [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus subtilis used in this study has several abilities to promote plant growth, such as the synthesis of phytohormones, biological nitrogen fixation, promotion of root and shoot development and increased productivity in several crops, such as soybean, maize, cotton and sugarcane ( dos Santos et al, 2018 ; Lobo et al, 2019 ; Shastri et al, 2020 ; Dos Santos et al, 2021 ; Escobar Diaz et al, 2021 ). However, in previous studies, the B. subtilis concentration used was 1 × 10 9 CFU ml −1 , and the fertilization dose was 100% the recommended dose for each crop.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies did not evaluate the effect of high inoculum concentrations on plant growth. Escobar Diaz et al (2021) assessed the impact of different inoculum concentrations, including B. subtilis , on cotton crops and did not find a difference between yield crops when the plants received the inoculum at 1 × 10 4 and 1 × 10 10 CFU ml −1 . However, these authors evaluated the effect of different inoculum concentrations at 100% of the fertilization dose, only.…”
Section: Discussionmentioning
confidence: 99%